IMPLEMENTASI METODE SOSTAS PADA INOVASI DIGITAL MARKETING PRODUK KRIPIK SALAK SEMERU - Irwanto, Jesi; Fauziah, Anisatul (Jurnal Multidisipliner Bharasumba, 2023)
This research has the objective of developing a digital marketing strategy for micro, small and medium enterprises making semeru lumajang salak chips. The qualitative methodological approach is a research approach, in which the data collection process is carried out through the observations of research respondents to obtain meaning related to the essential phenomena that occur. The results of the research that has been carried out are "Implementation of the SOSTAC Method in Digital Marketing Innovation of Semeru Salak Chips Products in micro, small and medium enterprises". Limited resources in interpreting online marketing mechanisms is a major problem that needs to be resolved immediately. In this case it is necessary to increase through training activities that are relevant and useful and appropriate for Krisameru micro, small and medium enterprises. This research is limited to semeru salak chips produced by MK Food Indonesia's micro, small and medium enterprises, Lumajang. From the implementation of this research, it can be used as a benchmark for other products in carrying out digital marketing innovations in the era of the world economy 4.0 so that in the future this research will be useful for all business actors in developing their businesses which will then directly and indirectly benefit the community.